Friends in High Places - Merrison, Lindsey (Lindsey Merrison Film ; Dschoint Ventschr, 2001)
Soros Documentary Fund Duration: 01:26:00 The film takes the viewer on a journey examining the extremes that define Burmese spirit mediums and their way of life. Whether contending with a deceitful daughter-in-law, forecasting financial prospects for a tea shop, or freeing a husband from government detainment, the film reveals the central role of “nats” and “spirit mediums” in alleviating the day to day burdens of modern life in Burma.